How should trichobezoar be treated in children? - Gülerman, Fulya; Güven, Burcu; Demir, Sabri; Özmen, İsmail (Turkish Journal of Gastroenterology, 2019)
Abstract Cite this article as: Gülerman F, Güven B, Demir S, Özmen İ. How should trichobezoar be treated in children? Turk J Gastroenterol 2019; 30(7): 660-1.